(untitled) (The Review of Diabetic Studies, 2024)
This study aimed to study the nurses knowledge and self-efficacy about the cardiopulmonary resuscitation at Al-Qunfudhah region, KSA. Knowledge is defined as the understanding, skill development, Apprehension, expertise enhancement, proficiency and realization regarding the Scenario, construct, event, or any other situation. Objective: This research aimed to assess the relationship between nurses’ knowledge and self-efficacy regarding the early initiation of CPR and automated defibrillation of cardiac arrest patients. Methods: The study measured the nurse’s knowledge regarding cardiopulmonary resuscitation, the adopted scale is consisting of 20 items with four-point response option with 5 subscales. Descriptive statistics and Pearson correlation used for data analysis. Results: Overall, the study sample showed very low knowledge regarding early initiation of CPR, compared to very high incorrect answer. Moreover, the participant respond (0.0%) for high score of knowledge. Conclusion: It is important for the nurses to be at a high level of skill and knowledge in this field. Because increasing levels of knowledge of nursing staff will support their own effectiveness.